The Rise of Special Purpose Acquisition Companies: Are SPACs a more effective means to enter public markets than their traditional IPO counterpart? - Whitehead, Adam (2022)
Special purpose acquisition companies (SPACs) have created an alternative means for companies to transition from private to public status. Their recent surge in 2019-2021 has left many wondering the motives behind using a SPAC vehicle in comparison to the traditional IPO method. This paper aims to provide a comprehensive and updated set of research in determining which method appears to be more effective under a set of circumstances. From observing 94 SPAC acquisitions and 771 IPOs over 2015-2020, we conclude that a high cost of debt significantly deters SPAC acquisitions, SPAC acquisitions facilitate existing investors to be able to sell their funds quicker and they can do so at more ease in comparison to IPOs, IPOs tend to take less time than SPAC acquisitions from the date of announcement, SPAC targets tend to be significantly smaller, and they are substantially more levered. In addition, we measure post-acquisition/IPO performance from the first date of public trading. Our results signal extreme underperformance for companies that chose the SPAC route, underperforming our benchmark market by 36.39% after 1 year.